Penetration, distribution and brain toxicity of titanium nanoparticles in rodents' body: a review - Zeman, Tomáš; Loh, El-Wui; Čierný, Daniel; Šerý, Omar (IET nanobiotechnology, 2018)
Titanium dioxide (TiO2) has been vastly used commercially, especially as white pigment in paints, colorants, plastics, coatings, cosmetics. Certain industrial uses TiO2 in diameter <100 nm. There are three common exposure routes for TiO2: (i) inhalation exposure, (ii) exposure via gastrointestinal tract, (iii) dermal exposure. Inhalation and gastrointestinal exposure appear to be the most probable ways of exposure, although nanoparticle (NP) penetration is limited. However, the penetration rate may increase substantially when the tissue is impaired. When TiO2 NPs migrate into the circulatory system, they can be distributed into all tissues including brain. In brain, TiO2 lead to oxidative stress mediated by the microglia phagocytic cells which respond to TiO2 NPs by the production and release of superoxide radicals that convert to multiple reactive oxygen species (ROS). The ROS production may also cause the damage of blood-brain barrier which then becomes more permeable for NPs. Moreover, several studies have showed neuron degradation and the impairment of spatial recognition memory and learning abilities in laboratory rodent exposed to TiO2 NPs.
Keywords: biologický transport; Tissue Distribution; Nanoparticles; reaktivní formy kyslíku; Biological Transport; mozek; Neurotoxicity Syndromes; Titanium; Reactive Oxygen Species; neurotoxické syndromy; Brain; Rodentia; zvířata; tkáňová distribuce; hlodavci; nanočástice; titan; Metal Nanoparticles; kovové nanočástice; Animals